Akibat Hukum dan Ketentuan Pemutusan Hubungan Kerja terhadap Pekerja yang Cacat dalam Kecelakaan Kerja - Zahra Alif Cendana Utama Ariyanto; Dipo Wahjoeono Hariyono (Jurnal Hukum Lex Generalis, 2024)
In a company, work accidents often occur due companies that don't pay attention work safety which ends in termination of employment, especially for workers who are disabled in work accidents, on the other hand, employers often do not fulfill their responsibilities, even the workers do not work anymore on the grounds of being less competent in their fields, workers who experience this are very unacceptable because it is difficult to get work for the future. Aims to understand the provisions for termination of employment for workers who are disabled in work accidents, the legal consequences for employers who do not take responsibility for the work accident, and legal protection for disabled workers in work accidents. This study applies normative law whose approach method is regulations and conceptualization, and the law studied literature review of secondary and will be primary law. The observation results explain this workers who become disabled due to work accidents are get the right to compensation costs such as medical treatment. Not only that, it includes compensation costs in legal relations where the company is obliged to provide workers' rights, namely to continue working for one year, provide compensation money, and to termination of employment is possible use the tripartite, bipartite, or Relation industri Court methods. The impact of employers who do not carry out procedures for terminating employment relationships is receive sanctions in the form of initial sanctions, fines and even criminal penalties.